An objective scoring method to evaluate image quality of middle cerebral artery Doppler. (1st February 2020) - Ruiz-Martinez, S.; Volpe, G.; Vannuccini, S.; Cavallaro, A.; Impey, L.; Ioannou, C.
Abstract: Objective: To validate an objective scoring system for middle cerebral artery (MCA) pulsed wave Doppler images. Method: From an image database of routine 36-week scans, a random sample of MCA Doppler images was selected. Two reviewers rated the images subjectively as acceptable or unacceptable. Subsequently they used an objective 6-point image scoring system and awarded one point for each of the following: (1) anatomical site, (2) magnification, (3) angle of insonation, (4) image clarity, (5) sweep speed adjustment, and (6) velocity scale and baseline adjustment. Image scores 4–6 were defined as good quality whereas 0–3 as poor. The subjective and objective agreement between the two reviewers was compared using the adjusted Kappa statistic. Results: A total of 124 images were assessed. Using objective scoring the agreement rate between reviewers increased to 91.9% (κ = 0.839) compared to subjective agreement 75.8% (κ = 0.516). The agreement for each criterion was: anatomical site 91.1% (κ = 0.823), magnification 95.2% (κ = 0.903), clarity 83.9% (κ = 0.677), angle 96.0% (κ = 0.919), sweep speed 98.4% (κ = 0.968), and velocity scale and baseline 94.4% (κ = 0.887). Conclusion: Objective assessment of MCA Doppler images using a 6-point scoring system has greater interobserver agreement than subjective assessment and could be used for MCA Doppler quality assurance.